The Effect of N-Acetylcysteine as Adjuvant Therapy of Hypoxemia in COVID-19 Patients, Assessed by Interleukin-6 Level and PaO2/FiO2 Ratio - Ngakan Putu Parsama Putra; Yani Jane Sugiri; Susanthy Djajalaksana; Aditya Sri Listyoko; Harun al Rasyid; Simon Petrus Hardiyanto Rumaratu (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Background: Interleukin 6 (IL-6) is a cytokine that plays an essential role in lung damage and mortality. Arterial-to-inspired oxygen (PaO2/FiO2) ratio, also known as the Horowitz index, is a measure of hypoxemia in respiratory failure. N-Acetylcysteine (NAC) might be helpful in managing coronavirus disease 2019 (COVID-19) patients by decreasing the cytokine storm, which will lead to a decrease in disease severity. This study aims to analyze the effect of NAC as adjuvant therapy on IL-6 level and PaO2/FiO2 ratio in COVID-19 patients.Methods: This is a quasi-experimental, non-equivalent control group designed study of confirmed COVID-19 patients moderate to critical in Saiful Anwar Hospital Malang. Seventy-five patients received NAC intravenously 5000mg/72 hours as adjuvant therapy for seven days, and 16 subjects in the control group. IL-6 level and PaO2/FiO2 ratio were measured on day one and day 8 in both groups from blood samples. Wilcoxon, Mann-Whitney U Test, and Pearson correlation were conducted for statistical analysis.Results: The decrease in IL-6 level on days 1 to 8 in the NAC group is significantly lower (94.49±253.51) than in the control group (P=0.002). The increase in PaO2/FiO2 ratio from day 1 to day 8 in the NAC group is significantly improving (126.94±76.05), the same as the control group (P<0.001). There is a weak correlation between IL-6 level and PaO2/FiO2 ratio after administration of NAC (r=0.154, P=0.186).Conclusion: There is a significant decrease in IL-6 level after administration of NAC. NAC has no significant effect on hypoxemia in COVID-19 patients.